The Effectiveness of Floortime Play Therapy on Improving Executive Functions and Cognitive Emotion Regulation in Children with Attention Deficit / Hyperactivity Disorder (ADHD) - Roghani, Farahnaz; Jadidi, Mohsen; Peymani, Javid (International Journal of Education and Cognitive Sciences, 2022)
This study aimed to determine the effectiveness of Floor time play therapy on improving executive actions and cognitive emotion regulation in children with attention deficit/hyperactivity disorder (ADHD). The research design was quasi-experimental with a pretest-posttest design and control group. The statistical population included all the 9-11 years-old boys with attention deficit/hyperactivity disorder (ADHD) who were referred to Counseling Centers and Psychological Services for Children in Tehran in the first half of 2018.. Data collection tools were Conners Parent Rating of Childhood Behavior Problems (CPRCBP) scale, Structured Clinical Interview, Barkley Deficits in Executive Functioning Scale-Children and Adolescents (BDEFS-CA), and Cognitive Emotion Regulation Questionnaire-Kids-Persian (CERQ-K-P). After performing the pre-test, the control group waited and the Floortime play therapy for the experimental group was performed in 10 sessions of 45 minutes in a group manner and then, at the end of the treatment interventions,. Research data were analyzed using Descriptive Statistics and Multivariate Analysis of Covariance (MANCOVA) and one-way analysis of covariance in the Manco context. The results showed that after the intervention, there was a significant difference between the experimental group and control group in the rate of increase in adaptive cognitive emotion regulation strategies of positive refocus and refocus on planning, and the rate of decrease in maladaptive cognitive emotion regulation strategies and insufficiency of executive actions (p 0.05).